Correlation between Axial Length and Retinal Nerve Fiber Layer Thickness in Myopic Eyes - Suhail Sarwar, Mumtaz Hussain, Muhammad Abdul Rehman, Irfan Qayyum Malik, Idress Ahmad (Pakistan Journal of Ophthalmology, 2018)
Purpose: To determine the correlation between axial length and retinal nerve fiber layer thickness in myopic eyes. Material and Method: One hundred patients of myopia with best corrected visual acuity of at least 6/12 in the best eye were included in this study. Optical coherence tomography was done with dilated pupils. Axial length was measured with A-Scan. After pupillary dilation, retinal nerve fiber layer thickness was measured with optical coherence tomography (OCT) around the center of optic disc. Mean retinal nerve fiber layer thickness was generated by automated computerized program in the analysis report and compared with the built in age-matched normative database in 3D OCT. Results: The mean age was 27.08 + 7.85 years. There were 50 males (50%) and 50 (50%) females. The mean spherical equivalent (myopia) was -2.95 D + 1.36. The mean axial length 23.92 + 0.614. The mean retinal nerve fiber layer (RNFL) thickness was 111.49 ?m + 4.04. Pearson coefficient of correlation was -.328. Conclusion: In myopic patients the RNFL thickness decreases with increasing axial length.